A New Normative Power in the North? A Comparative Analysis of the European Union‘s 2016 and 2021 Arctic Policies - Arnar Númi Sigurðarson 1995- (2022)
The Arctic region is changing rapidly. These changes stem mostly from climate change, as the Arctic is now warming four times faster than any other region on earth. Many actors in the international community have sought to band together to avoid climate catastrophe. Others see opportunity in the melting ice, as a warmer Arctic will create opportunities for oil and gas drilling and new shipping routes. Due to this fact, many actors are competing for these future opportunities. The EU has shown official interest in the Arctic since 2008. The first comprehensive EU Arctic policy came in 2016, followed by the most recent Arctic “communication” in 2021. This thesis provides a comparative analysis of the two policies in order to understand how the EU aims to participate in the Arctic and engage in Arctic politics. The thesis argues that compared with the 2016 EU Arctic policy, the 2021 EU Arctic document constitutes a radical improvement, as a far more comprehensive, integrated and better constructed approach to the Arctic. The 2021 document directly references Russia’s and China Arctic activities while discussing security, an important step as the two latter actors are often perceived as competitors to the EU in the Arctic and beyond. The 2021 communication advocates banning all new oil- and gas drilling in the Arctic, which other actors do not support. Miklar breytingar eru að eiga sér stað á norðurslóðum. Áhrif hnattrænnar hlýnunar valda því að norðurslóðir eru að hlýna fjórum sinnum hraðar en nokkuð annað svæði á jörðinni. Vegna þessa hafa hin ýmsu ríki bæði innan og utan norðurslóða sóst eftir að hjálpast að við að koma í veg fyrir yfirvofandi hörmungar sem fylgja frekari hlýnun norðurslóða. Mörg þeirra sjá þó líka tækifæri til þess að sölsa undir sig jarðefnaeldsneytisauðlindir, skipaleiðir og fiskistofna sem finnast á svæðinu. Þetta þýðir að talsverð samkeppni er nú þegar hafin um yfirráð á norðurslóðum. Evrópusambandið (ESB) hefur verið tiltölulega tregt til að mynda sér afgerandi stefnu varðandi ...